Determinants of Financial Inclusion among Smallholder Farmers in Zimbabwe - Masuka, Authur; Rukasha, Tanyaradzwa; Tatsvarei, Simbarashe (Journal of Agricultural Policy, 2025)
Purpose: Financial inclusion is critical for improving rural livelihoods, yet many farmers remain excluded due to various socioeconomic and systemic barriers. This study examines the factors influencing financial inclusion among smallholder farmers in Zimbabwe, focusing on access to formal financial services. Methodology: The study employs a binary logistic regression model to analyze data collected from smallholder farmers, assessing the impact of financial literacy, education, age, gender, household size, and farm characteristics on financial participation. Results indicate that while 94.4% of farmers achieve basic financial inclusion, only 25.6% access multiple financial services. Findings: Financial literacy emerges as the most significant determinant, with limited education, large household sizes, and gender disparities having a negative effect. Systemic barriers, including high transaction costs and inadequate rural banking infrastructure, further hinder inclusion. The study highlights the importance of targeted financial literacy programs, gender-sensitive financial products, and improved rural financial infrastructure. Unique Contribution to Theory, Policy and Practice: Policy recommendations include expanding mobile banking services, reducing transaction costs, and fostering collaboration between financial institutions and policymakers. Future research should assess the long-term impact of financial literacy initiatives and effectiveness of digital financial services in enhancing inclusion. Strengthening financial access can improve the resilience of smallholder farmers, thereby contributing to sustainable agricultural development and economic growth in Zimbabwe.